EFEK ANTIHIPERKOLESTEROLEMIA KITIN CANGKANG UDANG WINDU (Penaeus monodon) SECARA INVIVO PADA KELINCI (Oryctolagus cuniculus) - Muammar Fawwaz (Fakultas Farmasi UMI, 2013)
The reasearch test effect anthypercholesterolemia Chytosan Windu Shrimp Shell with aimed to know the effect to decrease the total blood cholesterol degree on adult rabbit. These research include 3 group, namely 1 group of control and 2 groups of examined namely chytosan 5% and 10% w/v. The observation applied with measure of the total blood cholesterol degree on adult rabbit before induction of cholesterol, then inducted of cholesterol as long as 7 days, then observed cholesterol degree, and then its gived chytosan 400 mg/kgBB (5%w/v) and 800 mg/kgBB (10%w/v) at the 8th and measured again of the total blood cholesterol degree after examined Chytosan at concentration 400 mg/kgBB (5%w/v) dan 800 mg/kgBB (10%w/v), conduct decreasing of total blood cholesterol degree on adult rabbit. Key Word : Antihypercholestrolemia, Penaeus monodo, Oryctolagus cuniculus, Invivo